Communication Strategy of State Security Sub Directorate of Security Intelligence Directorate of South Sulawesi Regional Police in Preventing Radicalism Ideology - Amrullah, M. Ishak Fauzan; Ar, Muhammad Yusuf; M, Rahmat Ferdiansyah (Borong Newinera Publisher, 2025)
This study aims to analyze the communication strategy of the South Sulawesi Regional Police in countering radicalism movements and to find factors that support and hinder the implementation of the South Sulawesi Regional Police's communication strategy in countering radicalism movements in Makassar City. The approach used in this study is a qualitative approach with a descriptive research strategy. This research was conducted at the Sub Directorate of State Security, Directorate of Security Intelligence, South Sulawesi Regional Police, which was carried out from February to March 2025. The informants in this study were 6 informants, namely, the Director and Deputy Director of Ditintelkam, Head of Sub Directorate of Kamneg Ditintelkam, Head of Unit 3, Intolerant and Radical Section, and 2 Police Members of Unit 3, Intolerant and Radical Section. The results of the study show that the communication strategy used by the Sub Directorate of State Security, Directorate of Security Intelligence, South Sulawesi Regional Police in preventing radicalism ideology in Makassar City consists of situational analysis, goal orientation, media selection, message development and evaluation. Supporting factors for the implementation of communication strategies in countering radical ideology are police personnel resources, synergy between the government, religious institutions, and community organizations, and the development of social media, while inhibiting factors for the implementation of communication strategies in countering radical ideology are differences in understanding and interpretation of radicalism, the spread of hoaxes and disinformation, and limited resources